Geochemical investigation of oils from Cretaceous to Eocene sedimentary sequences of the Abadan Plain, Southwest Iran. (May 2016) - Alizadeh, Bahram; Saadati, Hossein; Rashidi, Mehrab; Kobraei, Mehdi
Abstract: Oil samples from Lower Cretaceous to Eocene reservoirs in southwest Iran were analyzed using gas chromatography–mass spectrometry and gas chromatography–isotope ratio mass spectrometry for genetic classification of oil families and determining their maturity. The Studied oil samples are non-biodegraded and their gravity range from 18.3 to 37° API. The slight even/odd n-alkane predominance, coupled with low Pr/Ph values, suggests their likely source rocks with a predominance of algal organic matter, type IIS kerogen deposited under strongly reducing marine environments. The biomarker distribution of investigated oils is characterized by high concentration of both C29 and C30 hopanes and ratios of C29 /C30 H are generally greater than unity. There is a marked predominance of C29 regular sterane over C27 and C28 homologs in our studied oils. High sterane/hopane values and cross plot of the δ 13 C sat versus δ 13 C aro show contribution of marine organic matter. Medium value of gammacerane index and other salinity indices show water density stratification and high salinity conditions of the environment of deposition. It can be concluded that the studied reservoirs, due to their variable maturity have different API gravity and contain two oil families (types A and B) with latter being deeper and comprising more mature oils. Highlights: GC-MS and GC-IRMS analyses were performed on the crude oil samples. The crude oil's probable source rocks were characterized. Based upon maturity, two oil families were identified. These non-biodegraded oils with variable maturities, have different API Gravities. Both A and B oil families are generated from Kerogen Type IIS.